Effect of gender‐affirming hormone use on coagulation profiles in transmen and transwomen. (22nd February 2021) - Scheres, Luuk J.J.; Selier, Nienke L.D.; Nota, Nienke M.; van Diemen, Jeske J.K.; Cannegieter, Suzanne C.; den Heijer, Martin
Abstract: Background: The transgender population that uses gender‐affirming hormone therapy (GAHT) is rapidly growing. The (side) effects of GAHT are largely unknown. We examined the effect of GAHT on coagulation parameters associated with venous thromboembolism (VTE) risk. Methods: Factor (F)II, FIX, FXI, protein (p)C and free pS, fibrinogen, hematocrit, sex hormone‐binding globulin, and normalized activated protein C ratio were measured in 98 transwomen (male sex at birth, female gender identity) and 100 transmen (female sex at birth, male gender identity) before and after 12 months of GAHT (oral or transdermal estradiol and anti‐androgens in transwomen, transdermal or intramuscular testosterone in transmen). Mean paired differences in coagulation measurements were estimated with 95% confidence intervals (95% CI). Differences for route of administration and age were assessed with linear regression. Results: After GAHT, transwomen had more procoagulant profiles with a mean increase in FIX: 9.6 IU/dL (95% CI 3.1–16.0) and FXI: 13.5 IU/dL (95% CI 9.5–17.5), and a decrease in pC: −7.7 IU/dL (95% CI −10.1 to −5.2). Changes in measures of coagulation were influenced by route of administration (oral vs. transdermal) and age. A higher sex‐hormone binding globulin level after 12 months was associated with a lower activated protein C resistance. In transmen, changes were not procoagulant overall and were influenced by age. Differences for route of administration (transdermal vs. intramuscular) were small. Conclusions: GAHT in transmen was not associated with apparent procoagulant changes, which provides some reassurance regarding VTE risk. In transwomen, GAHT resulted in procoagulant changes, which likely contributes to the observed increased VTE risk.